Seepage and stability of slope with capillary barrier system - Feng, Xin Yu (2015)
Capillary barrier system (CBS) is a soil cover system which consists of two layers of soil with distinct hydraulic properties to minimize rainwater infiltration into the underlying soil. Capillary barrier system can acts as a preventive measure in preventing rainfall-induced slope failures. In this study, the capillary barrier system was used as a cover system for a residual soil under the rainfall intensity of 18mm/h with 24 hour duration. The capillary barrier system designed in this study used the fine recycled crushed asphalt (RCA) as the fine-grained layer and coarse RCA as the coarse-grained layer. Both seepage and slope stability analyses were performed and the effect of surface drains on the performance of CBS was investigated in this study. The numerical results showed that the CBS was capable in minimizing rainwater infiltration into the slope and capable of maintaining negative pore-water pressures under rainfalls. The presence of surface drains within the capillary barrier system was helpful to prevent the breakthrough in the coarse-grained layer of the CBS. CBS was proven to be an effective method for improvement of rainfall-induced slope.